PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2012-2016) - Yunina, Yunina; Husna, Asmaul (Department of Accounting, Faculty of Economics & Business, 2018)
This study aimed to determine the effect of capital structure and financial performance on the value of the company. The data of this research were taken from 70 observations. The population of this research was manufacturing companies of Food and Beverage sub-sector which listed on Indonesia Stock Exchange in 2012-2016 . The number of samples used in this study was 14 companies taken using Cencus sampling technique. .The method of data analysis used in this study was multiple linear regression analysis. The results of this study indicate that the capital structure had a negative effect on the company value and financial performance had a positive effect on company value. Suggested: For investors to pay attention to the profitability and capital structure generated by the company so that it can obtain a higher return.